Archiwum Norbertanek w Imbramowicach - Dębowska, Maria (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The Norbertine Sisters Convent in Ibramowice was founded at the beginning of the 13th century. It has survived until the present day; in the 15th century the nuns were transferred to Busko for some time, so it was only once in its history that this nunnery existed outside Ibramowice. The archive of the convent suffered considerable losses over centuries: in 1710 the church and the convent were consumed by fi re, in 1820 the convent was deprived of its manors and, in consequence, it was divested of a large number of the most precious records. At present the archive in Ibramowice consists of several archival collections. The open collection comprises the documentation of the convent office in Ibramowice (“The Norbertine Sisters Convent in Ibramowice”). The rest collections are the ones to which documentation is no longer added. They contain a certain number of archival units, including: 1) the remnants of the offi ce documentation of the nunneries -the Norbertine and Cistercian Sisters- from which the nuns were resettled in Ibramowice in the 19th and at the beginning of the 20th centuries, 2) the legacy of different people who were somehow connected with the convent in Ibramowice (e.g. chaplains). The majority of the archival collection of the Norbertine Sisters in Ibramowice is on microfilm.